Juris Stage sebagai Panggung Ekspresi Mahasiswa Hukum Universitas Harkat Negeri - Prasetya Putra Nugraha; Nur Baiti Rahman (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Freedom of expression is a fundamental human rights to seek, receive, and disseminate information or ideas freely, and its existence is regulated by the constitution. Freedom of expression can be done in various forms, one of them is art. Art is a part of human creative expression that presents beauty, involving skill, and bringing out the sensitivity of the heart. Juris Stage provides room for movement for undergraduate law department students Universitas Harkat Negeri in carrying out social criticism throught art. The research method used was a qualitative approach targeting Undergraduate law department students from class of 2025. The results of the study show that Juris Stage participants express his social criticism through music, poetry, and stand up comedy where each material contains criticism of problems that exist around. With the existence of the Juris Stage it is hoped that there is institutional support, students awareness, and community involvement to create synergy between students and the community in solving social problems.